1894
DOI: 10.1002/qj.4970209204
|View full text |Cite
|
Sign up to set email alerts
|

Fogs reported with strong winds during the 15 years 1876‐90 in the British Isles

Abstract: TEYPERITURES AT ORONEBOURNE, 1880-89. 263 satisfy himself on this point he had a special thermometer constructed and buried in the soil, its bnlb being two feet below the surface, and compared its indications with those from a thermometer placed in an iron tube (the umal form of earth thermometer) a t a similar depth in the ground. The results of this comparison showed that the indications of the two instruments accorded very closely, the thermometer in contact with the soil reading about O " 5 lower in col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…In this study, the maximum values obtained regarding the wind speed analysis are as follows: 20 and 25 kt in LTCT; 16 kt in LTCF, and 26 kt in LTCO. These maximum wind values obtained are in parallel with Scott's study (Scott, 1894).…”
Section: Resultssupporting
confidence: 84%
“…In this study, the maximum values obtained regarding the wind speed analysis are as follows: 20 and 25 kt in LTCT; 16 kt in LTCF, and 26 kt in LTCO. These maximum wind values obtained are in parallel with Scott's study (Scott, 1894).…”
Section: Resultssupporting
confidence: 84%
“…He also mentioned that the strong wind fogs were accompanied by rain which was frequently heavy. SCOTT (1894) showed that fog occurrence was correlated to strong winds (Beaufort scale of 6), and that there was no clear relationship between weather patterns (e.g., cyclonic or anticyclonic) and fog formation. Scott also stated that the total number of fog cases with strong wind was (1992) carried out the Po Valley Fog Experiment which was a joint effort by several European research groups from five countries.…”
Section: Introductionmentioning
confidence: 99%
“…A historical dense foggy event was reported by Scott in 1896, stating that fogs with strong winds accompanied by heavy rain occurred in the British Isles. Fog-related events associated with strong winds are estimated to be about 135 in 15 years [41,42]. In 1892, fog formation was found to be related to the role of aerosols.…”
Section: Fog Forecastingmentioning
confidence: 99%